An experimental study on flexural performance of reinforced geopolymer concrete beams - Kumar, S. Sundar; Ahmed, Md Adil; Srinivasan, V.; Maheswaran, S. (Journal of Structural Engineering, 2024)
Geopolymer concrete has emerged as a viable alternative to Portland cement concrete in recent years. Binders in geopolymer concrete are distinctively different from those in Portland cement concrete. The variation in properties of a geopolymer matrix can be high since the raw materials used are industrial wastes with essentially no control over their composition. This necessitates a complete characterization of the material as well as a thorough study of its mechanical, durability and structural properties. In this study, the flexural performance of reinforced geopolymer concrete beams designed as per Indian standards has been experimentally studied. The results though vindicate the use of geopolymer concrete in structural members, it has revealed that the structural behaviour of reinforced geopolymer concrete can distinctively differ from that of reinforced concrete beams made with Portland cement concrete. Results reported here indicate a reduced ductility in reinforced geopolymer concrete beams. Revision in the provisions of current concrete codes may be necessary. Relation between the properties of geopolymer concrete and the raw materials used in them needs to be thoroughly documented.